ON STRONG AND WEAK HYPER KS-IDEALS OF DECOMPOSABLE HYPER KS-SEMIGROUPS - Tabaranza, Georgie F.; Vilela, Jocelyn P. (Italian Journal of Pure and Applied Mathematics, 2015)
This paper extends the study of hyper KS-semigroups, an algebraic hyperstructure which is a combination of hyper BCK-algebra and semihypergroups with respect to some hyperoperations to the concept of decomposable hyper KS-semigroups. We introduce the concept of strong and weak hyper KS-ideals and present some of their properties. Furthermore, we establish the idea of decomposable hyper KS-semigroups in the context of strong, weak and hyper KS-ideals, give conditions for decomposable hyper KS-semigroups, investigate its properties and structure and provide some characterizations.